Quality Journey of Turkey from the Perspective of Language Teachers - Köksal, Hayal (Journal of NELTA, 2012)
Interest in quality improvement efforts has boomed during the past decade. Total Quality Management (TQM) based upon “PDCA (Plan-Do-Check-Act) Mindset” originated in the business world but it has gained tremendous popularity in educational institutions in recent years. The philosophy and practice of Quality education have become the center of discussions in academe across the world, especially in universities. This article focuses on the launching of the Quality Campaign in Turkey where all state schools under the Ministry of Education first adopted the campaign in 1999, but then largely resisted its implementation because it was perceived and often practiced as a top-down process. More recently, one of the most fundamental changes occurred in ELT (English Language Teaching) classes through the leadership of ELT teachers in a bottom-up approach. The aim of this paper is to provide a historical review of Quality Education in Turkey and share some insights with readers about its implementation. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6129 NELTA 2011; 16(1-2): 52-58